Lattice Study of QCD Phase Structure by Canonical Approach - Bornyakov V.G.; Boyda D.; Goy V.; Molochkov A.; Nakamura A.; Nikolaev A.; Zakharov V.I. (EPJ Web of Conferences, 2018)
The canonical approach is a powerful tool to circumvent sign problem in LQCD. Although it has its own difficulties it provides opportunity to determine QCD phase transition line. Using improved Wilson fermions we calculated number density at nonzero imaginary chemical potential for confinement and deconfinement phases, restored canonical partition functions Zn and did extrapolation into the real chemical potential region. We computed the higher moments of the baryon number including the kurtosis, and compared our results with information from relativistic heavy ion collision experiments.